Admission and Registrar Office (ARO) Mobile Document Scanner with Archiving System - Mallares, Dinalyn; Alegata, Wayne Custer; Bual, Joel (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Archive document scanning refers to the procedure of converting physical paper records into digital formats, such as images or text files, and establishing a systematic workflow to preserve and access these archived files electronically over an extended period [1]. With the growing acceptance of mobility and digitalization worldwide, institutions such as libraries, government offices, museums, and universities are increasingly adopting document scanning as means to safeguard and preserve historical documents and records. This approach is particularly valuable in preventing the natural degradation and aging of physical documents, as highlighted by Scan2Archive [2]. The purpose of the Admission and Registrar Office (ARO) Mobile Document Scanner with Archiving System is to support the registrar’s office in managing student requests and admissions as well as handling the documents that are presented during the enrollment. The office of the registrar will experience a transformation in document handling with the development of a document archiving system, which will promote operational excellence, security, and transparency. With the help of this system, the office’s procedures for managing vital records—such as student transcripts, enrollment requirements, and other important paperwork—will be completely transformed. The basis for the development of the system is transforming paper-based records into a digitally accessible format. In evaluating the effectiveness of the application and the system’s operation it specified the performance requirements for the software evaluation. The star topology was used as part of the communication interfaces. The thirty (30) respondents tabulated the data in each of the different features of the system are accuracy, user-friendliness, reliability, operability, learning reinforcement, interactivity, compatibility, and the cross-platform environment was rated as "excellent”. The application was made to help the whole process become much more convenient to the admin and staff of the university.